Molecular epidemiology and mechanisms of carbapenem and colistin resistance in Klebsiella and other Enterobacterales from treated wastewater in Croatia - Ana Puljko; Ivan Barišić; Svjetlana Dekić Rozman; Stela Križanović; Ivana Babić; Marko Jelić; Ana Maravić; Nikolina Udiković-Kolić (Environment International, 2024)
Among the most problematic bacteria with clinical relevance are the carbapenem-resistant Enterobacterales (CRE), as there are very limited options for their treatment. Treated wastewater can be a route for the release of these bacteria into the environment and the population. The aim of this study was to isolate CRE from treated wastewater from the Zagreb wastewater treatment plant and to determine their phenotypic and genomic characteristics. A total of 200 suspected CRE were isolated, 148 of which were confirmed as Enterobacterales by MALDI-TOF MS. The predominant species was Klebsiella spp. (n = 47), followed by Citrobacter spp. (n = 40) and Enterobacter cloacae complex (cplx.) (n = 35). All 148 isolates were carbapenemase producers with a multidrug-resistant phenotype. Using multi-locus sequence typing and whole-genome sequencing (WGS), 18 different sequence types were identified among these isolates, 14 of which were associated with human-associated clones. The virulence gene analysis of the sequenced Klebsiella isolates (n = 7) revealed their potential pathogenicity. PCR and WGS showed that the most frequent carbapenemase genes in K. pneumoniae were blaOXA-48 and blaNDM-1, which frequently occurred together, while blaKPC-2 together with blaNDM-1 was mainly detected in K. oxytoca, E. cloacae cplx. and Citrobacter spp. Colistin resistance was observed in 40% of Klebsiella and 57% of Enterobacter isolates. Underlying mechanisms identified by WGS include known and potentially novel intrinsic mechanisms (point mutations in the pmrA/B, phoP/Q, mgrB and crrB genes) and acquired mechanisms (mcr-4.3 gene). The mcr-4.3 gene was identified for the first time in K. pneumoniae and is probably located on the conjugative IncHI1B plasmid. In addition, WGS analysis of 13 isolates revealed various virulence genes and resistance genes to other clinically relevant antibiotics as well as different plasmids possibly associated with carbapenemase genes. Our study demonstrates the important role that treated municipal wastewater plays in harboring and spreading enterobacterial pathogens that are resistant to last-resort antibiotics.